Meta-Analysis: Effect of Acupuncture Therapy on HbA1c Levels in Type II Diabetes Mellitus - Wahyu, Fatimah; Prasetya, Hanung; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Diabetes mellitus is a chronic condition that occurs when there is an increase in glucose levels in a person's blood because the body cannot produce enough of the insulin hormone, or cannot use the insulin it produces effectively. This study aims to estimate the effect of acupuncture therapy on changes in HbA1c in people with type II diabetes mellitus. Subjects and Method: This research is a systematic review and meta-analysis carried out using the PRISMA flow diagram and PICO model including Population = Type II diabetes patients; Intervention = Acupuncture Therapy; Comparison= No acupuncture therapy or sham acupuncture; Outcome= Change in HbA1c and quality of life. Article searches through journal databases include: PubMed, Science Direct, Google Scholar, Springer Link, BMC and Hindawi. Search keywords: acupuncture, AND